Towards the Determination of the Quality of Argumentative Essays From the Lexical-Grammatical Analysis of Their Introductions (Revista de Estudos da Linguagem, 2024)
An evaluative writing genre that presents difficulties for university students is the argumentative essay (AE). This article aims to relate the quality of the introductions to the quality of the AEs, considering their lexical-grammar features. To achieve this, we selected 96 AEs, produced in two phases during one academic term. Then, we compared both phases of the evaluation of the AEs and their introductions (IEA), as well as their lexical-grammar features. Subsequently, we correlated the AE data with their AEIs. Finally, we performed a clustering analysis, according to lexical-grammar patterns. The findings indicate a) significant differences between AEs and AEIs of both phases, b) distinctive lexical-grammar patterns between both phases, c) a high correlation between AE and AEI quality, and d) a continuum of quality between introductions. Between the phases, we observed an improvement in the quality of the AEIs not only from the argumentative point of view but also according to the characteristics of the discursive genre. Furthermore, the importance of this macro-move as a predictor of content quality is proven. These results are useful for the early detection of difficulties in academic writing.